Evaluation of business activity of a construction firm - Savenko, V.I.; Nesterenko, I.S.; Savenko, S.S.; Orlik, Yu.V. (Ways to Improve Construction Efficiency, 2020)
The assessment of current production activities is carried out on the example of specialized construction and installation management with the help of turnover indicators as well as the level of efficiency of use of own and borrowed funds by the enterprise was determined. Indicators of this group characterize the results and efficiency of the current main activity of the enterprise, such analysis can be carried out both at the qualitative level and with the help of quantitative criteria. The main ones are production indicators, return on assets and turnover indicators. These indicators are of great importance for assessing the financial condition of the enterprise, because the speed of turnover, i.e. the speed of their conversion into cash, directly affects the solvency. The results of the calculation of the rate of return indicate that this fact (decrease in the turnover of fixed assets) may be associated with aging and wear of production equipment, i.e. we can say that the technical level of fixed assets of the object is low. The coefficient of sustainability of economic growth shows the average rate at which the company can develop further, without changing the already established relationship between different sources of funding. Summarizing the comparative data, we can say that if the management of the enterprise intends to increase its production capacity in order to increase production, it is necessary to change the financial policy. The results of calculations allow to show that at the analyzed enterprise there was a significant increase in the full production cycle and turnover as a whole. The duration of the operating cycle increased by more than 1.2 times and the duration of the financial cycle by almost 2 times. This was negatively affected by the factor of a significant slowdown in the turnover of inventories. Increasing the full production cycle in the future may cause negative trends in the enterprise as a whole, because this factor will primarily affect the amount of profit, which will affect the efficiency of production. The company activities to reduce the amount of net profit was influenced primarily by the acquisition of inventories, low-value perishable items and fixed assets, as well as repayment of accounts payable and payment of penalties. The period of turnover of the most liquid assets during the year varied from 0.04 to 17.5 days. The average chronological value in the period of saving money in the accounts of the enterprise was 7.5 days. This fact indicates that the company, despite the apparent well-being, is experiencing a serious shortage of funds. They were enough for a little over a week. Thus, with the help of analysis of economic indicators, you can describe the general condition of the company and the possibilities of its operation and development